2003
DOI: 10.1002/ana.10596
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in autistic patients with 15q inverted duplication

Abstract: Two autistic children with a chromosome 15q11‐q13 inverted duplication are presented. Both had uneventful perinatal courses, normal electroencephalogram and magnetic resonance imaging scans, moderate motor delay, lethargy, severe hypotonia, and modest lactic acidosis. Both had muscle mitochondrial enzyme assays that showed a pronounced mitochondrial hyperproliferation and a partial respiratory chain block most parsimoniously placed at the level of complex III, suggesting candidate gene loci for autism within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 20 publications
3
124
0
Order By: Relevance
“…In several studies of individuals presenting with autism, but without classical mitochondrial disease, increased ammonia has also been described; this led some authors to conclude that MtD was present [40,63,64] . Typically, these ammonia levels are not nearly as elevated as those that have been observed in some conditions that can cause autism, such as urea cycle disorders [66] .…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies of individuals presenting with autism, but without classical mitochondrial disease, increased ammonia has also been described; this led some authors to conclude that MtD was present [40,63,64] . Typically, these ammonia levels are not nearly as elevated as those that have been observed in some conditions that can cause autism, such as urea cycle disorders [66] .…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%
“…However, many of these laboratory abnormalities have also been described in autistic individuals with MtD and without any other evidence of classical mitochondrial disease. For example, elevated blood lactate levels consistent with MtD have been described in numerous autistic individuals [29,40,[61][62][63][64][65] , sometimes affecting as many as 43% of children with autism studied when compared to neurotypical children [17] . In one study, ASD children with an elevated blood lactate level underwent deltoid muscle biopsy and approximately 35% (5 out of 14) were found to have classical mitochondrial disease [22] .…”
Section: Biomarkers Of Classical Mitochondrial Disease and Mtd In Autmentioning
confidence: 99%
“…A number of cases of mitochondrial respiratory chain (MRC) disorders have been described associated with autism, including a child with autism and documented MRC complex IV deficiency by Lászlo, Horvath, Eck, and Fekete (1994), an autistic boy and his sister with Leigh syndrome with MRC complex IV defect and a mitochondrial DNA (mtDNA) G8363A mutation (Graf et al, 2000), two autistic children with 15q inverted duplication, mitochondrial hyperproliferation and respiratory complex III defect (Filipek et al, 2003) and five patients with autism and mtDNA mutations or mtDNA deletion (Pons et al, 2004). In a previous population-based study of autistic children in Portugal (Oliveira et al, 2005), we have found hyperlactacidemia, a biochemical marker of mitochondrial dysfunction, in 20.3% of 69 tested patients.…”
Section: Introductionmentioning
confidence: 99%
“…22 Investigations into causes of elevated oxidants have pointed to mitochondrial dysfunction in autistic patients. 7,23 The role of mitochondria in the electron transport system (ETS) makes them the major source of oxidants and primary targets of free radicals (FRs). 24 Free radicals are highly toxic to neurons and they are generated significantly in the human brain, which is extremely sensitive to oxidative stress.…”
Section: Resultsmentioning
confidence: 99%